Faktor-Faktor yang Mempengaruhi Adopsi Aplikasi Go-Pay Menggunakan UTAUT2 - Deny . (ULTIMA InfoSys, 2019)
E-money adoption can lead to faster ecommerce business development in the country. Unfortunately, e-money adoption percentage in Indonesia is still very far behind developed countries. Therefore, more studies about e-money adoption determinant factors in Indonesia are needed to improveadoption. Sample of this study was 422 Go-Pay users in Indonesia, taken by online form. The data was analized using SEM technique by Lisrel. Result shows that use intention of e-money is determined by hedonic motivation, social influence, habit and price value. Performance expectancy, effort expectancy, and facilitating conditions were found not significant factorsof use intention of e-money. Interestingly, the real usage of e-money is not determined by facilitating conditions but still significantly influenced by habit and use intention of e-money. Result of this study are useful for e-money entrepreneurs who need to improve e-money application usage in Indonesia by focusing on providing features and incentives for user enjoyment and social influence.